Relationship between Dark Triad, Mental Health, and Subjective Well-being Moderated by Mindfulness: A Study on Atheists and Muslim Students - Aamer Aldbyani; Mohammed Hasan Ali Al-Abyadh (Islamic Guidance and Counseling Journal, 2022)
Research indicates that mindfulness is related to mental health (anxiety, depression, and general health) and well-being. However, its impact on individuals who have the Dark Triad (DT) personality remains unclear. We examined the relationship between the DT constructs (narcissism, psychopathy, and Machiavellianism), mental health, and subjective well-being with mindfulness as the moderator variable. A total of 764 (Atheist=412; Muslims=352) university students were recruited to complete the Dark Triad personality scale (DM), Mindful Attention Awareness Scale (MAAS), Beck Depression Inventory-II (BDI-II), Trait Anxiety scale (STAI), General Health Questionnaire (GHQ), and Subjective Well-Being scale (SWB). Pearson's correlations and PROCESS macro were used to evaluate associations between these variables and whether mindfulness moderated the associations between DT constructs, mental health, and subjective well-being. The results revealed that DT statistically significant predictor of mental health but only in low mindfulness levels. While two DT constructs, narcissism and Machiavellianism, significantly predict subjective well-being only for participants with high mindfulness levels.